1965
DOI: 10.1139/v65-279
|View full text |Cite
|
Sign up to set email alerts
|

THE CHEMISTRY OF D-APIOSE: PART II. THE CONFIGURATION OF D-APIOSE IN APIIN

Abstract: The tri-0-methyl-D-apiose derivative obtained from the hydrolysis products of tnethylated apiin was found to be identical with 2,3,4-tri-0-methyl-D-apio-D-furanose prepared synthetically. Periodate oxidation studies support the suggested cis relationship of the hydroxyl groups a t Cn and Ca of the apiose moiety in apiin, and consideration of optical rotation data suggest that a &type linkage unites the D-apiosyl unit to Cz of the D-glucopyranose residue in apiin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1968
1968
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…[ P P~I Literaturwerte van Decurosid IV, aufgenommen in (D,)DMSO; es werden nur die S, des Zucker-Restes aufgefuhrt [7]: die Losungsmittel-Verschiehung betragt hei Vergleich der Apiose-Reste -3 ppm ( 7-0 -@-D-Glucopyranosyl)apigenin [9] hergeleitet werden'). Aus der in der Grossenordnung dem [MI, des Methyl-glycosids von P-D-Apiose ([MI, = -405" [9]) ahnlichen Differenz zwischen Di-und Monoglycosid der beiden Substanzpaare wurde fur den Apiosyl-Rest in 1 P-D-Konfiguration abgeleitet.…”
Section: 6unclassified
See 1 more Smart Citation
“…[ P P~I Literaturwerte van Decurosid IV, aufgenommen in (D,)DMSO; es werden nur die S, des Zucker-Restes aufgefuhrt [7]: die Losungsmittel-Verschiehung betragt hei Vergleich der Apiose-Reste -3 ppm ( 7-0 -@-D-Glucopyranosyl)apigenin [9] hergeleitet werden'). Aus der in der Grossenordnung dem [MI, des Methyl-glycosids von P-D-Apiose ([MI, = -405" [9]) ahnlichen Differenz zwischen Di-und Monoglycosid der beiden Substanzpaare wurde fur den Apiosyl-Rest in 1 P-D-Konfiguration abgeleitet.…”
Section: 6unclassified
“…Aus der in der Grossenordnung dem [MI, des Methyl-glycosids von P-D-Apiose ([MI, = -405" [9]) ahnlichen Differenz zwischen Di-und Monoglycosid der beiden Substanzpaare wurde fur den Apiosyl-Rest in 1 P-D-Konfiguration abgeleitet. (7) und H-C(9) ableiten: 3 zeigt fur H-C (9) und H-C (7) …”
Section: 6unclassified
“…14) Because 4 and 5 showed negative and positive optical rotations, respectively, 4 and 5 should be the (3S,6S)-and (3S,6R)-forms. Therefore 4, 5, 6, and 7 were characterized as (3S,6S)-6,7-dihydroxy-6,7-dihydrolinalool, (3S,6R)-6,7-dihydroxy-6,7-dihydrolinalool, (3S,6S)-6,7-dihydroxy-6,7-dihydrolinalool 3-O-b-D-glucopyranoside, and 6,7,18) apiose was confirmed to be the D-form. Therefore 9 was characterized as (1R,4S,6S)-…”
mentioning
confidence: 99%
“…50, No. 4 9) suggested that 6 was a b-D-apiofuranoside of 5. Thus, 6 was characterized as (1S,2S,4R)-p-menth-8- ϩ ion peak at m/z 153 in the positive FAB-MS. Enzymatic hydrolysis of 7 gave 6a and D-glucose, and thus, 7 was suggested to be a monoglucoside of 6a.…”
mentioning
confidence: 99%